Exploration of the Analgesic and Antipyretic Effects of Mangosteen Peel Methanol Extract (Garcinia mangostana L) in Male Wistar Rats - Jiang Fan; Florenly Florenly; Liena Liena; Fioni Fioni (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Analgetic-antipyretic is a compound that is often used to reduce pain and fever. A natural plant that has the potential as an antipyretic analgesic compound is mangosteen fruit (Garcinia mangostana L). This study aims to find out the analgesic and antipyretic effects of mangosteen peel methanol extract on male Wistar rats. This type of research is experimental, design Post-Test Only Control Group Design. The research was conducted at the Pharmaceutical Laboratory of the University of North Sumatra Medan, January - March 2021. The test was conducted using 25 mice divided into 5 groups. Data analysis uses SPSS test one-way ANOVA if the data does not distribute normal Kruskal-Wallis. The results of the study 5 hours after treatment, the body temperature of the mice experienced a significant change, the value of P < 0.05 (Value P = 0.004). Where the methanol extract group of mangosteen skin III showed the lowest body temperature 5 hours after treatment which was 36.14 ± 0.12oC and the methanol extract group Mangosteen-III skin also showed a significant difference to the control group that showed the highest body temperature of 37.36 ± 0.46oC. The least amount of geliat found in the mangosteen-III skin methanol extract group was 5.22 ± 1.91 and this number showed a significant difference with the mangosteen- I skin methanol extract group (12.81 ± 3.12) and the control group (11.10 ± 1.91). In conclusion, the results of mangosteen skin testing have antipyretic and antipyretic effects, found at 5 hours after treatment and the highest dose is 750 mg/ kgBB. Meanwhile, the results of the hematologic examination showed a significant decrease in line with the increase in the dose of mangosteen skin methanol extract given.